2008
DOI: 10.1128/iai.00096-08
|View full text |Cite
|
Sign up to set email alerts
|

Glycogen and Maltose Utilization by Escherichia coli O157:H7 in the Mouse Intestine

Abstract: Mutant screens and transcriptome studies led us to consider whether the metabolism of glucose polymers, i.e., maltose, maltodextrin, and glycogen, is important for Escherichia coli colonization of the intestine. By using the streptomycin-treated mouse model, we found that catabolism of the disaccharide maltose provides a competitive advantage in vivo to pathogenic E. coli O157:H7 and commensal E. coli K-12, whereas degradation of exogenous forms of the more complex glucose polymer, maltodextrin, does not. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
127
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(129 citation statements)
references
References 48 publications
1
127
1
Order By: Relevance
“…Again, this is in contrast to the findings of Jones et al (45), which showed that maltose was important for E. coli colonization of the mouse intestine. These authors also found, in contrast to our previous findings, that glycogen was a significant carbon source (57).…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…Again, this is in contrast to the findings of Jones et al (45), which showed that maltose was important for E. coli colonization of the mouse intestine. These authors also found, in contrast to our previous findings, that glycogen was a significant carbon source (57).…”
Section: Discussioncontrasting
confidence: 56%
“…Despite the shortcomings of this approach, the patterns of expression were closer to our preconceptions than we imagined. Similarly, patterns of global gene transcription in Campylobacter jejuni in a similar model were found to resemble those in older birds with gut floras (92), and other similar models (e.g., a streptomycintreated mouse) have been used with E. coli with success (15,44,45). The requirement for a large number of chickens to generate sufficient RNA also meant that bacteria present in the ceca of different birds would also likely have been present at different stages of the growth cycle, depending on whether the ceca were full, had just emptied, or were freshly filled (P. Barrow, un- a Ten chickens were inoculated with the test strain.…”
Section: Discussionmentioning
confidence: 99%
“…A transposon mutant deficient in these activities was identified and tentatively mapped to the operon homologous to the E. coli malEFG maltose/maltodextrin transporter. This high-affinity ABC transporter system consists of a periplasmic maltosebinding protein encoded by malE and a transport complex encoded by malF, malG and malK (Jones et al, 2008b). On the basis of the transport functions of the operon, it was hypothesized that malEFG is necessary for proper colonization and utilization of coral mucus by the pathogen.…”
Section: Discussionmentioning
confidence: 99%
“…Extensively studied in E. coli, this transporter system has been shown to be present in many bacterial species, both gram-positive and gram-negative, including Enterococcus faecalis, Staphylococcus aureus, Streptococcus pneumoniae, Bacillus subtilis, Listeria monocytogenes, and Vibrio cholera (17). The maltodextrin transporter has also been implicated in the virulence mechanisms of some of these pathogens (18)(19)(20)(21). The transporter is a complex of 5 proteins with the outer membrane maltoporin (LamB) and the periplasmic maltose binding protein (MalE) serving as the key determinants of transporter specificity (17).…”
mentioning
confidence: 99%